Desafios e perspectivas da Web semântica - Canalle, Gabrielle Karine (2013)
The Web is now a tangle of information is disorganized, making it difficult to perform tasks on the network, how to search for information. The Semantic Web is an attempt at solution to this clutter and other web problems. Emerged as a new internet concept that aims to allow greater interaction between machine and user. Its main objective is to give meaning to information, causing computers and people to work in better cooperation. To do this, is based on three pillars, the language XML (Extensible Markup Language), the syntax RDF (Resource Description Framework) and Ontologies. Although it is considered the future of the Web, the Semantic Web still has many challenges to overcome. This final project aimed to present the challenges and prospects of the Semantic Web, identifying the current web problems, and what you can change with the use of the Semantic Web in conjunction with other associated technologies.